Etymological aspects of a phraseosemantic field - Trybukhanchyk, А.М. (Видавництво НДУ ім. Миколи Гоголя, 2018)
The article is devoted to the analysis of etymological sources of a phraseosemantic field in English with the general meaning of man’s material state in a historical perspective. Taking into account the information of etymological and explanatory dictionaries it was found that for the most part phraseological units of the field "richness-poverty" go down to traditions, customs, the way of life of English people. Besides, units of terminological origin occupy a considerable place. Among borrowed units the first in quantity are idiomatic expressions originating from the regional variants – American and Australian English.
Keywords: phraseological unit; phraseosemantic field; native English